Games, Ludi & Ethos: considerações sobre a imersão em modelagens realistas - Leite, Gilles Pedroza (2017)
In this text we will travel through a critical exposition of the three-dimensional effects in movies and games development history creating a relation between the immersive factor and the technique of its production, we will seek to clarify how its developments, both aesthetic and technological, are reinventing the importance of image in contemporary society. Therefore, we will begin to show the context of production and levels of immersion, then move on to introduce an analytical look about the same. We will pass through the concepts of procedural modeling used in the industry of games, and the preference on its use on implementing the creation for vegetation landscapes. Then we elucidate these points through the game analysis The Witcher III, especially the landscape and vegetation through a match with the real tree that meet the aesthetic characteristics of the chosen object in the game